2022
DOI: 10.51507/j.jams.2022.15.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Warm Cupping of the Posterior Thorax in Combination with Standard Conventional Therapy for ARDS in COVID-19 Patients in ICU: a Case Series

Abstract: Acute respiratory distress syndrome (ARDS) is commonly found in critically ill patients with coronavirus disease 2019 (COVID-19). As a non-pharmacological treatment of complementary and alternative medicine (CAM), cupping has been clinically used for respiratory symptoms. We sequentially identified a series of patients with COVID-19 with ARDS who were admitted to the intensive care unit (ICU). Warm cupping of the posterior thorax was performed for seven days. We collected longitudinal severity scores on cough,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Clinical studies have shown that patients with COVID-19 with acute respiratory distress syndrome (ARDS) who undergo posterior thoracic cupping therapy 21 times experience improvements in symptoms including cough, breathlessness, chest tightness and SpO 2 levels. Notably, these patients did not require mechanical ventilation after discharge, indicating that integrating cupping therapy with conventional treatment may offer a favourable prognosis for individuals with acute respiratory conditions 14. Although the mechanism of cupping therapy for SP remains unclear, there are indications that cupping therapy may improve lung function and inflammatory cytokine levels in patients with SP.…”
Section: Discussionmentioning
confidence: 93%
“…Clinical studies have shown that patients with COVID-19 with acute respiratory distress syndrome (ARDS) who undergo posterior thoracic cupping therapy 21 times experience improvements in symptoms including cough, breathlessness, chest tightness and SpO 2 levels. Notably, these patients did not require mechanical ventilation after discharge, indicating that integrating cupping therapy with conventional treatment may offer a favourable prognosis for individuals with acute respiratory conditions 14. Although the mechanism of cupping therapy for SP remains unclear, there are indications that cupping therapy may improve lung function and inflammatory cytokine levels in patients with SP.…”
Section: Discussionmentioning
confidence: 93%
“…Similar results were shown in our case series that evaluated the effectiveness cupping in COVID-19 patients. The case series suggests that warm cupping of the posterior thorax is effective in improving respiratory symptoms and reducing mortality and intubation in COVID-19 patients with ARDS 37 . Furthermore, a case report by Cheng demonstrated amelioration of dyspnea and chest tightness in a COVID-19 patient with cupping 38 .…”
Section: Discussionmentioning
confidence: 95%
“…In a clinical study, warm cupping of the posterior thorax was applied with conventional treatments for 7 days in 8 patients who suffered from COVID-19 with acute respiratory destress syndrome (ARDS). Improvement of the symptoms severity scores was reported in all patients who were discharged without the need for mechanical ventilation [187].…”
Section: Cupping Therapymentioning
confidence: 86%